2015
DOI: 10.1371/journal.pone.0138447
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Diversity of Cpt1 Genes in Vertebrate Species

Abstract: The Carnitine palmitoyltransferase I (Cpt1) gene family plays a crucial role in energy homeostasis since it is required for the occurrence of fatty acid β-oxidation in the mitochondria. The exact gene repertoire in different vertebrate lineages is variable. Presently, four genes are documented: Cpt1a, also known as Cpt1a1, Cpt1a2; Cpt1b and Cpt1c. The later is considered a mammalian innovation resulting from a gene duplication event in the ancestor of mammals, after the divergence of sauropsids. In contrast, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Interestingly, the absence of CPT 1γ was discovered in fish species including grass carp. Lopes-Marques et al (2015) reassessed the evolutionary relationships of CPT family and suggested that the first duplication in the ancestor of vertebrates generated CPT 1 and CPT 2, and the second duplication of CPT 1 gene in vertebrates resulted in CPT 1α, CPT 1β, and CPT 1γ. However, the teleost fish lost CPT 1γ, and the chondrichthyes lost CPT 1β as a result of the special energy metabolism among vertebrates (Lopes-Marques et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the absence of CPT 1γ was discovered in fish species including grass carp. Lopes-Marques et al (2015) reassessed the evolutionary relationships of CPT family and suggested that the first duplication in the ancestor of vertebrates generated CPT 1 and CPT 2, and the second duplication of CPT 1 gene in vertebrates resulted in CPT 1α, CPT 1β, and CPT 1γ. However, the teleost fish lost CPT 1γ, and the chondrichthyes lost CPT 1β as a result of the special energy metabolism among vertebrates (Lopes-Marques et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in fish, the isoforms CPT 1α and CPT 1β were identified and characterized in previous studies on trout and sea bream (Boukouvala et al, 2010;Morash et al, 2008;Morash and McClelland, 2011). Interestingly, teleosts possess multiple isoforms of the CPT gene family, including CPT 1α1a, CPT 1α1b, and CPT 1α2a (Wu et al, 2016;Zheng et al, 2013), which might result from a unique evolutionary history in fish that involves genome duplication (Lopes-Marques et al, 2015;Morash et al, 2010).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Fatty acid synthase is a multifunctional enzyme that catalyses FA biosynthesis (lipogenesis) in the cytoplasm of adipocytes and hepatocytes (Liu et al, ). Finally, CPT1C is a brain‐specific enzyme involved in the regulation of ketogenesis (production of ketonic bodies during fat metabolism) (Lee & Wolfgang, ; Lopes‐Marques et al, ; McPherson & McEneny, ), and plays a crucial role in ‐oxidation of FA, facilitating the initial step in the transfer of acyl to the mitochondrial matrix (Price et al, ; Toral et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies on lipogenic genes in fish address the characterization and tissue‐specific distribution of CPT1; these have been conducted in rainbow trout ( Oncorhynchus mykiss , Walbaum 1792) (Gutierres, Damon, Panserat, Kaushik, & Medale, ) and yellow catfish ( Pelteobagrus fulvidraco , Richardson 1846) (Zheng, Luo, Zhu, Chen, & Gong, ). Additionally, Boukouvala, Leaver, Favre‐Krey, Theodoridou, and Krey () characterized the CPT1B gene based on muscle tissue cDNA in seabream ( Sparus aurata , Linnaeus 1758), and Lopes‐Marques et al () examined the evolutionary history of the CPT1 gene family in vertebrate species, using amino acid (AA) sequences of several fish species under a comparative genomics approach. The molecular characterization and tissue expression of ACC1 gene was determined for grass carp ( Ctenopharyngodon idella , Valenciennes 1844) (Cheng et al, ).…”
Section: Introductionmentioning
confidence: 99%